Model Kolaborasi Lembaga Keuangan dan Universitas Dalam Memperkuat Akses Layanan Keuangan Mikro dan Kinerja Usaha Mikro dan Kecil di Indonesia: A Model of Collaboration of Financial Institutions and Universities in Strengthening Access To Microfinance Services And The Performance of Micro and Small Enterprises in Indonesia - Suhendi; Achsani, Noer Azam; Najib, Mukhamad; Novianti, Tanti (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Micro and Small Enterprises (MSEs) have an important and strategic role in national economic development. This study aims to identify and analyze problems in the implementation of microfinance services for MSEs in Indonesia and develop a collaborative model involving relevant stakeholders, especially financial institutions and universities, to support microfinance and improve the performance of MSEs in Indonesia. The research method used in this research is Soft Systems Methodology (SSM), utilizing data from FGDs, in-depth interviews, and observations. The results of the study show that financing constraints for MSEs can be seen from two perspectives, namely the MSEs themselves (demand side) and financial institutions (supply side). Collaborative models between various stakeholders, especially between financial institutions and universities, can be an alternative solution to strengthen access to microfinance services and improve the performance of micro and small businesses in Indonesia. In terms of transaction cost theory, universities can reduce the transaction costs of financial institutions through research, education, innovation, and partnerships with financial institutions. Therefore it can be concluded that collaboration between universities and financial institutions can make a valuable contribution to developing more efficient and cost-effective solutions in the financial industry, especially in increasing access to microfinance services and the performance of MSEs in Indonesia. Keywords: catwoe, collaborative intervention, financial system, rich picture, soft system methodology